Further Delineation of the Clinical Phenotype of Cerebellar Ataxia, Mental Retardation, and Disequilibrium Syndrome Type 4. (26th February 2018) - Alsahli, Saud; Alrifai, Muhammad Talal; Al Tala, Saeed; Mutairi, Fuad Al; Alfadhel, Majid
Background: Cerebellar ataxia, mental retardation, and disequilibrium syndrome (CAMRQ) is a heterogeneous group of genetic disorders that have been grouped by shared clinical features; all of these features are transmitted via an autosomal recessive mechanism. Four variants of this syndrome have been identified so far, and each one differs in terms of both clinical and genotypical features. CAMRQ4 is a rare genetic disorder characterized by mental retardation, ataxia or an inability to walk, dysarthria and, in some patients, quadrupedal gait. Methods: We investigated three Saudi families with CAMRQ4. Blood samples were collected from the affected patients, their parents, and healthy siblings. DNA was extracted from whole blood, and whole-exome sequencing was performed. Findings were confirmed by segregation analysis, which was performed on other family members. Results: Thus far, 17 patients have been affected by CAMRQ4. Genetic analysis of all patients, including our current patients, showed a mutation in the aminophospholipid transporter, class I, type 8A, member 2 gene ( ATP8A2 ). A series of common phenotypical features have been reported in these patients, with few exceptions. Ataxia, mental retardation, and hypotonia were present in all patients, consanguinity in 90% and abnormal movements in 50%. Moreover, 40% achieved ambulation at least once in their lifetime, 40% had microcephaly, whereas 30% were mute. Magnetic resonance imaging (MRI) of the brain was normal in 60% of patients. Conclusions: We described the largest cohort of patients with CAMRQ4 syndrome and identified three novel mutations. CAMRQ4 syndrome should be suspected in patients presenting with ataxia, intellectual disability, hypotonia, microcephaly, choreoathetoid movements, ophthalmoplegia, and global developmental delay, even if brain MRI appears normal.